2022
DOI: 10.1108/jec-07-2021-0099
|View full text |Cite
|
Sign up to set email alerts
|

Let’s be entrepreneurs – Finnish youth’s attitudes toward entrepreneurship

Abstract: Purpose The purpose of the study is to clarify Finnish youth’s attitudes toward entrepreneurship and evaluate both regional and background factors influencing those attitudes. Design/methodology/approach The authors conducted a survey of 1,497 students aged 15 to 24 years and analyzed the data using descriptive statistical analysis. Findings The study’s results indicate positive attitudes toward entrepreneurship among the youth. One of the notable findings of the study was the number of students who had al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…Sin embargo, la mayoría resalta la necesidad de formarse primero. Esto es particularmente importante en provincias, donde la acción educadora fomenta la intención empresarial (Hintikka et al, 2022), posiblemente ocasionado por la ausencia de un entorno que motive emprender.…”
Section: Tabla 1 Modelo De Verosimilitudunclassified
“…Sin embargo, la mayoría resalta la necesidad de formarse primero. Esto es particularmente importante en provincias, donde la acción educadora fomenta la intención empresarial (Hintikka et al, 2022), posiblemente ocasionado por la ausencia de un entorno que motive emprender.…”
Section: Tabla 1 Modelo De Verosimilitudunclassified
“…Interest in entrepreneurship as an encouragement and desire to try or run a business [9]. While according to [10] interest is an innate inclination or attraction towards something or an activity without external prompting or instruction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, attitudes towards entrepreneurship are also considered essential predictors of entrepreneurial intention [10]. It has even been suggested that positive and negative perceptions of entrepreneurship are more important than cognitive factors in influencing entrepreneurial intention [11]. Similarly, it has been suggested that entrepreneurial intention influences students' entrepreneurial inclinations [12].…”
Section: Introductionmentioning
confidence: 99%